2020
DOI: 10.1101/2020.06.09.134460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rare Deletion in SARS-CoV-2 ORF6 Dramatically Alters the Predicted Three-Dimensional Structure of the Resultant Protein

Abstract: The function of the SARS-CoV-2 accessory protein p6, encoded by ORF6, is not fully known. Based upon its similarity to p6 from SARS-CoV, it may play a similar role, namely as an antagonist of type I interferon (IFN) signaling. Here we report the sequencing of a SARS-CoV-2 strain passaged six times after original isolation from a clinical patient in Hong Kong. The genome sequence shows a 27 nt in-frame deletion (Δ27,264-27,290) within ORF6, predicted to result in a 9 aa deletion (ΔFKVSIWNLD) from the central po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
(23 reference statements)
4
20
0
Order By: Relevance
“…Additionally, we found that the subgenomic RNAs of ORF6, ORF7 and ORF8 were dramatically decreased in the P10-trVLP infected cells compared with that of P1 VLP (Fig. 3E), indicating that ORF6, ORF7 and ORF8 may not be required for virus infection at least in vitro, consistent with other reports that deletions of these regions were observed in clinical samples by deep sequencing analysis [17][18][19][20] .…”
Section: Characterization Of the Genetic Stability Of Sars-cov-2-gfp/supporting
confidence: 90%
“…Additionally, we found that the subgenomic RNAs of ORF6, ORF7 and ORF8 were dramatically decreased in the P10-trVLP infected cells compared with that of P1 VLP (Fig. 3E), indicating that ORF6, ORF7 and ORF8 may not be required for virus infection at least in vitro, consistent with other reports that deletions of these regions were observed in clinical samples by deep sequencing analysis [17][18][19][20] .…”
Section: Characterization Of the Genetic Stability Of Sars-cov-2-gfp/supporting
confidence: 90%
“…Here, we characterized large ORF6 deletion variants identified through surveillance of patients from the same hospital unit. Reports of similar patterns of genomic deletions in the SARS-CoV-2 genome since its emergence have already been described, including in the ORFs 6,7,and 8 [20,21,29,32].…”
Section: Discussionmentioning
confidence: 91%
“…Non-synonymous mutations cause amino acid substitutions, and could alter virus protein structures, which may affect viral reproduction, leading to false-negative diagnoses and drug resistance. It is reported that the depletion of nine amino acids in SARS-CoV-2 Orf6 resulted in a dramatic alteration of protein structure and caused a shift in its transmembrane localization, which would lead to drug resistance of interferon (IFN) [4].…”
Section: Introductionmentioning
confidence: 99%